2010
DOI: 10.1186/1471-2458-10-253
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic impact of rotavirus vaccination in GAVI-eligible countries

Abstract: BackgroundRotavirus infection is responsible for about 500,000 deaths annually, and the disease burden is disproportionately borne by children in low-income countries. Recently the World Health Organization (WHO) has released a global recommendation that all countries include infant rotavirus vaccination in their national immunization programs. Our objective was to provide information on the expected health, economic and financial consequences of rotavirus vaccines in the 72 GAVI support-eligible countries.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 46 publications
2
52
0
Order By: Relevance
“…3842 It is important to note that the unique purpose of these global analyses is not to provide accurate cost-effectiveness estimates for a given country, but to give an indication of what the plausible range of cost-effectiveness is likely to be for countries in a particular region/income strata, and to identify the most important determinants of cost-effectiveness for those countries. An alternative approach could have been to run the analysis for all countries separately, as in the studies by Kim et al and Goldie et al 39,42 However, this level of disaggregation could be misleading because a number of country-specific estimates are generated without any primary data collection. If cost-effectiveness estimates are to have any real influence on decision-making at country-level, countries need to have ownership over the data, assumptions, and results of the model.…”
Section: Discussionmentioning
confidence: 99%
“…3842 It is important to note that the unique purpose of these global analyses is not to provide accurate cost-effectiveness estimates for a given country, but to give an indication of what the plausible range of cost-effectiveness is likely to be for countries in a particular region/income strata, and to identify the most important determinants of cost-effectiveness for those countries. An alternative approach could have been to run the analysis for all countries separately, as in the studies by Kim et al and Goldie et al 39,42 However, this level of disaggregation could be misleading because a number of country-specific estimates are generated without any primary data collection. If cost-effectiveness estimates are to have any real influence on decision-making at country-level, countries need to have ownership over the data, assumptions, and results of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus vaccination may be a very cost-effective intervention [9], [10], [11], [12], [13] and [14] which could save up to 2.5 million lives over the next 20 years in Global Alliance for Vaccines and Immunization(GAVI)-eligible countries [10]. Countryspecific benefits from rotavirus vaccination will depend on the specific burden of diarrhea, vaccine price and efficacy, and the targeting of the vaccination programs [9], [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This is the first study that assesses competing choices of rotavirus vaccines and is a significant update to previous reports because new evidence on diarrheal burden of disease has recently emerged. The most important finding of our study shows that rotavirus vaccination is justified in most world countries.…”
Section: Discussionmentioning
confidence: 89%
“…Although those previous analyses have shown that rotavirus vaccination is costeffective in some low-income and middle-income countries, [1][2][3][4][5] no study has attempted to highlight possible differences in costeffectiveness for these 2 vaccines. Also, new rotavirus vaccines are in development, showing promising preliminary results.…”
Section: Estimated Cost-effectiveness In Global Vaccinementioning
confidence: 94%
See 1 more Smart Citation